Alternative human eIF5A protein isoform plays a critical role in mitochondria. Issue 5 (18th January 2021) - Pereira, Karina D.; Tamborlin, Letícia; de Lima, Tanes I.; Consonni, Silvio R.; Silveira, Leonardo R.; Luchessi, Augusto D.
Abstract: The eukaryotic translation initiation factor 5A (eIF5A) is the only known protein containing the amino acid residue hypusine, essential for its activity. Hypusine residue is produced by a posttranslational modification involving deoxyhypusine synthetase and deoxyhypusine hydroxylase. Herein, we aimed to describe the role of the alternative human isoform A on mitochondrial processes. Isoform A depletion modulates oxidative metabolism in association with the downregulation of mitochondrial biogenesis‐related genes. Through positive feedback, it increases cell respiration leading to highly reactive oxygen species production, which impacts mitochondrial bioenergetics. These metabolic changes compromise mitochondrial morphology, increasing its electron density and fission, observed by transmission electron microscopy. This set of changes leads the cells to apoptosis, evidenced by increased DNA fragmentation and proapoptotic BAK protein content increase. Thus, we show that the alternative eIF5A isoform A is crucial for energy metabolism controlled by mitochondria and cellular survival. Abstract : Isoform A depletion modulates oxidative metabolism in association with the downregulation of mitochondrial biogenesis‐related genes. The alternative eukaryotic translation initiation factor 5A (eIF5A) isoform A is crucial for energy metabolism controlled by mitochondria and cellular survival.